Interview as a Learning Technique in Speaking Subject: Students’ Perspective - G, Hasriani (Universitas Negeri Semarang, 2019)
Speaking is one of the important skills of language. In teaching speaking, there are some techniques that can be used by the lecturers. One of the is interview technique. Interview is a communication process that uses questions and answers in response. Interview is effectively used in learning speaking because it can stimulate the brain to think. In the interview process, the interviewer reveals the question and the interviewee listens then responds to the question. This study aims to determine the perspective of students about interview as a learning technique on speaking subject applied by the lecturers. This is a qualitative descriptive study. Data were collected through questionnaires and interviews on research subjects. The data collected were analysed qualitatively by describing the phenomena occurring in the field during the course of the study. The subjects of this research were sixth semester students majoring in English Education, Faculty of Languages and Literature, Universitas Negeri Makassar, who have passed the Speaking subject. Based on the results of the study, interview is a good technique in learning speaking. Some students argued that through interview technique, speaking skill of the students would increase. In addition, through interview technique, someone could socialize with others because of the interaction. This technique was also believed to increase students' confidence in speaking. Through this technique, students would be trained in the use of English in everyday life, for example when applying for a job.